The Influence of Recruitment on Employee Performance at PT Toarco Jaya Toraja Utara - Panimba, Riska; Sambara, Kordiana; Rasinan, Djusniati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Study This aiming For analyze influence recruitment to performance employees at PT. Toarco Jaya North Toraja. In the dynamics competition the coffee industry is growing competitive , effective recruitment strategies become crucial For to obtain source Power quality human beings . Approach quantitative used in study This with involving 30 respondents employee as total sampling. Data is collected through questionnaire and analyzed using the Pearson correlation test , the coefficient determination , and partial t-test . The results of the study show that recruitment influential significant to performance employees , with mark coefficient correlation of 0.402 (p = 0.028) and the coefficient determination by 16.1%. The t-test shows t- value count of 2.321 > t- table (2.048), which strengthens significance influence recruitment to performance . Findings This confirm that the recruitment process is structured , fair and transparent can increase quality work and commitment employees . Implications practical from study This is importance evaluation and development sustainable to system recruitment in frame push productivity organization in a way comprehensive .